Will the development of smart agriculture improve food safety in international markets? A theoretical approach - Meziani, Lamia; Radjef, Mohammed Said; Perito, Maria Angela; Hammoudi, Abdelhakim (Frontiers in Sustainable Food Systems, 2024)
We propose a theoretical model to analyze the role of smart agriculture in the ability of countries to comply with international food safety regulations, specifically the Maximum Residue Limits (MRLs) for contaminants such as aflatoxins, pesticides, and heavy metals. However, there is currently a significant "digital divide" in the agricultural sector between developing and developed countries. This disparity has negative consequences on the international competitiveness of these countries and their ability to comply with MRLs. Firstly, we show that reducing the digital divide will always improve international food safety and food security (availability of a global supply). However, it can lead to more intense international competition, potentially causing a perverse effect: underinvestment in good agricultural practices by more digitally advanced countries. Furthermore, the digital catch-up of less advanced countries cannot sufficiently reduce health risks in international markets unless accompanied by strengthening official food control systems. Finally, we show that such digital catch-up encourages lowering MRLs rather than relaxing them, contrary to what producers or authorities might hope.